Pembangkit Listrik Tenaga Air Ubrug Sukabumi: PLTA Kolonial Hindia Belanda dan Fungsinya (1917–1925) - Muhammad Gibran Humam Fadlurrahman (Badan Riset dan Inovasi Nasional (BRIN), 2023)
This article discusses the Ubrug Hydroelectric Power Plant (PLTA) in Sukabumi which was constructed as part of the development of Dutch irrigation engineering and the modernization of the colony as an implementation of the Ethical Policy in the early 20th century. The Ubrug hydropower plant has been planned since 1917 for electricity needs in Batavia and its surroundings, Buitenzorg, and Sukabumi. Construction began in 1918 and became operational in 1925. This research focuses on the construction of the Ubrug Hydropower Plant and its function in the context of the development of colonialism in the Dutch East Indies in the early 20th century in the period 1917-1925. This research uses historical methods consisting of heuristic, verification, interpretation, and historiography. This research shows that the construction of the Ubrug hydropower plant cannot be separated from the context of the historical development of irrigation engineering and Ethical Policy, as well as an effort to modernize the Dutch East Indies, especially for the electrification of railway lines.